To form or not to form: PuO2 nanoparticles at acidic pH. Issue 4 (11th March 2022) - Gerber, Evgeny; Romanchuk, Anna Yu.; Weiss, Stephan; Kuzenkova, Anastasiia; Hunault, Myrtille O. J. Y.; Bauters, Stephen; Egorov, Alexander; Butorin, Sergei M.; Kalmykov, Stepan N.; Kvashnina, Kristina O.
Abstract : The combination of advanced spectroscopic and microscopic methods used in this work enables molecular and atomic levels understanding of the Pu(iv ) nanoparticles formation under acidic conditions (pH 1–4). Abstract : The aim of this study is to synthesize PuO2 nanoparticles (NPs) at low pH values and characterize the materials using laboratory and synchrotron-based methods. Properties of the PuO2 NPs formed under acidic conditions (pH 1–4) are explored here at the atomic scale. High-resolution transmission electron microscopy (HRTEM) is applied to characterize the crystallinity, morphology and size of the particles. It is found that 2 nm crystalline NPs are formed with a PuO2 crystal structure. High energy resolution fluorescence detected (HERFD) X-ray absorption spectroscopy at the Pu M4 edge has been used to identify the Pu oxidation states and recorded data are analysed using the theory based on the Anderson impurity model (AIM). The experimental data obtained on NPs show that the Pu(iv ) oxidation state dominates in all NPs formed at pH 1–4. However, the suspension at pH 1 demonstrates the presence of Pu(iii ) and Pu(vi ) in addition to the Pu(iv ), which is associated with redox dissolution of PuO2 NPs under acidic conditions. We discuss in detail the mechanism that affects the PuO2 NPs synthesis under acidic conditions and compare it with one in neutral and alkaline conditions. Hence, the results shown here, together with the first Pu M4 HERFD data on PuF3 and PuF4 compounds, are significant for the colloid facilitated transport governing the migration of plutonium in a subsurface environment.